IMPLEMENTASI PP NOMOR 53 TAHUN 2010 TENTANG DISIPLIN PNS DI KECAMATAN TOHO KABUPATEN PONTIANAK - Bayu Supianto E.42008051 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
AbstractThe purpose in writing about skripsi is a to describe Government of Rule Number 53 Year2012 in District Office Toho in Pontianak Region. This skripsi to write based on indisipliner problemand respected of the rule. This research use of descriptif kualitative models and to describe how toimplementation government of rule Number 53 years 2012 About Dicipline of Cipil GovernmentWorkers. The location of this research in Toho District in Pontianak Region. Subj ect of research is aworkers government in District Toho Office. Main of the point from this research is a theimplementation of government rule not good because of communication factors such as, transmitionthen resources of human like as staff and facilit y and respected of human to the government rule. Therecommended from this research is to law of hard who to croos of discipline, to added facilit y ofdistrict office and to added worker of government for district office.Key Words: Implementation, Communication, Human Resources, Dispotition, Beuractice ofStructure